2015
DOI: 10.1007/s13187-015-0955-4
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Ambassadors: Enhancing a Theory-Informed Training Program for Informed Decision-Making

Abstract: Despite the high burden of prostate cancer in African American communities, there is a paucity of knowledge about prostate health. This paper describes the enhancement of a curriculum for training lay health advisors, called prostate cancer ambassadors, on informed decision-making for prostate cancer screening. Adult learning theory informed the structuring of the training sessions to be interactive, self-directed, and engaging. Trainings were developed in a manner that made the material relevant to the learne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The present study used a single group, pretest-posttest design to assess the training and outreach outcomes of the Prostate Cancer Ambassador Informed Decision-Making training program, whereby the curriculum utilizes principles of adult learning theory (e.g., Knowles, Holton, & Swanson, 2015), which informed the interactive manner in which material was presented to the Ambassadors, and social cognitive theory (e.g., Bandura, 1986), which emphasized building self-efficacy for presenting the material to the community. The details of the development of the training program and its curriculum have been fully described elsewhere (Vines et al, 2015). The original training was developed for African Americans by African American community leaders, though it was refined by a multiethnic team of researchers and community members.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study used a single group, pretest-posttest design to assess the training and outreach outcomes of the Prostate Cancer Ambassador Informed Decision-Making training program, whereby the curriculum utilizes principles of adult learning theory (e.g., Knowles, Holton, & Swanson, 2015), which informed the interactive manner in which material was presented to the Ambassadors, and social cognitive theory (e.g., Bandura, 1986), which emphasized building self-efficacy for presenting the material to the community. The details of the development of the training program and its curriculum have been fully described elsewhere (Vines et al, 2015). The original training was developed for African Americans by African American community leaders, though it was refined by a multiethnic team of researchers and community members.…”
Section: Methodsmentioning
confidence: 99%
“…The Prostate Cancer Ambassador Informed Decision-Making training program was designed to be implemented over a 2-day training period for a total of 12 hours (Vines et al, 2015). A community partner with a history of grassroots community education efforts co-facilitated the sessions with the CHE and doctoral student.…”
Section: Ambassador Trainingmentioning
confidence: 99%
“…There is some variety in the definition of "peer-to-peer" (P2P) interventions in the literature, but the major commonalities are that they involve individuals (e.g. peer educators) who are members of the target community, who are natural helpers, natural leaders, a person others trust and typically turn to for support, and someone who has a large social network (17- 19). The role of peer educators is to promote the health of community members by providing health information, resources, or referrals in an informal, and culturally relevant way (19)(20)(21).…”
Section: Peer-to-peer Programsmentioning
confidence: 99%
“…Many studies have looked at the effectiveness of training peer educators, and generally found training to be effective at increasing the knowledge of peer educators(19, 24-26, 34, 39) and in some cases creating positive behavior change in the peer educators themselves(26,34). Training sessions improve the self-efficacy and retention of individual educators(19,23,26). A leadership team that prioritizes providing quality education to the chosen peer educators is a key component of P2P initiatives.…”
mentioning
confidence: 99%